Institutional and Empowerment Models of Integrated Zakāh Village in Jember - Agus Mahardiyanto; Moehammad Fathorrazi; Lusiana Ulfa Hardinawati (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2022)
Indonesia has a significant zakāh potential. However, the challenges faced by zakāh management are related to the collection and distribution. This research aims to analyze the institutional patterns and empowerment models of the Integrated Zakāh Village in Jember using the Participatory Rural Appraisal (PRA) theory. Using observations, a document study, Focused-Group Discussions (FGD), and in-depth interviews with the zakāh stakeholders, this research assesses the compatibility of the PRA theory in the development of Kampung Zakāh. This study finds that the obstacles in the Zakāh Village program are related to mustaḥiq's work ethics and enthusiasm. Among the aspects that need to be improved is the promotion of the program through social media to make it a massive community movement. Furthermore, this program empowers marginalized groups, including women, and encourages them to be independent.